In vivo Effects in Melanoma of ROCK Inhibition-Induced FasL Overexpression - Teiti, Iotefa; Florie, Bertrand; Pich, Christine; Gence, Rémi; Lajoie-Mazenc, Isabelle; Rochaix, Philippe; Favre, Gilles; Tilkin-Mariamé, Anne-Françoise (Frontiers in Oncology, 2015)
Ectopic Fas-ligand (FasL) expression in tumor cells is responsible for both tumor escape through tumor counterattack of Fas-positive infiltrating lymphocytes, and tumor rejection though inflammatory and immune responses. Our team has previously shown that RhoA GTPase and its effector ROCK kinases negatively control FasL membrane expression in murine melanoma B16F10 cells. In this study we found that B16F10 treatment with the ROCK inhibitor H1152 reduced melanoma development in vivo through FasL membrane over-expression. Although H1152 treatment did not reduce tumor growth rate in vitro, the inhibitor delayed tumor appearance and slowed tumor growth in C57BL/6 immunocompetent mice in vivo. Thanks to the use of mice bearing mutated Fas receptors (B6/lpr), we found that reduced tumor growth, observed in immunocompetent mice, was linked to FasL over-expression induced by H1152 treatment. Tumor growth analysis in immunosuppressed NUDE and IFNγ-KO mice highlighted a major role for T lymphocytes and IFNγ in the H1152-induced tumor growth reduction. Histological analyses of subcutaneous tumors, obtained from untreated versus H1152-treated B16F10 cells, showed that H1152 pretreatment induced a strong intra-tumoral infiltration of lymphocytes. Cytofluorometric analysis showed that these were mainly activated CD8 lymphocytes, which were responsible for the reduction in tumor growth. Subcutaneous tumor growth was also reduced by repeated intravenous injections of a clinical ROCK inhibitor Fasudil. Finally, H1152-induced ROCK inhibition also reduced pulmonary metastasis implantation, but this effect was not dependent on the T cell-mediated immune response. Altogether our data show that B16F10 melanoma cell treatment with ROCK kinase inhibitors, reduces tumor growth and metastasis development and through increased FasL expression, promotes an anti-tumor immune response. These inhibitors could therefore become interesting pharmacological molecules for melanoma immunotherapy.